Indications and Surgical Outcome Following Pulmonary Metastasectomy: A Nationwide Study - Vidarsdottir, Halla; Moller, Pall H.; Jonasson, Jon G.; Pfannschmidt, Joachim; Gudbjartsson, Tomas (The Thoracic and Cardiovascular Surgeon, 2012)
Aim The aim of this retrospective nationwide study was to investigate indications and surgical outcome after pulmonary metastasectomy (PM) in a well-defined cohort of patients and to calculate the proportion of cancer patients who were operated on.Methods Between 1984 and 2008, 81 patients (age 54.8 years, 50.6% men) underwent 100 PMs with curative intent in Iceland. For all patients, information on demographics, number of metastases, type of surgery, and complications were collected. Overall survival was estimated with median follow-up of 45 months. For the three most common malignancies, the proportion of patients who underwent PM was calculated using information from the Icelandic Cancer Registry on all cases diagnosed.Results Of 100 PMs, there were 62 wedge resections, 34 lobectomies, and 4 pneumonectomies. The most common complication was persistent air leakage (>96 hour; 11.1%), and operative mortality was 1.2%. Of the 12 kinds of primary malignancies operated, three were most common: colorectal carcinoma (CRC, n = 27), sarcoma (n = 21), and renal cell carcinoma (RCC, n = 14). The proportion of patients who underwent PM was 1.0% for CRC, 6.5% for sarcoma, and 1.4% for RCC, and their 5-year overall survival was 45.2, 18.6, and 38.5%, respectively (p = 0.11). Survival for all patients was 30.8%.Conclusion The surgical outcome and survival of patients who underwent PM in Iceland are comparable to those in the other studies. Although there was no control group and selection bias cannot be eliminated, the survival of PM patients was better than for the nonoperated patients. However, a relatively small proportion of patients with CRC, RCC, and sarcoma underwent metastasectomy.
Keywords: metastasectomy; pulmonary metastases; colorectal cancer; renal cell cancer; sarcoma; survival